Analisis Self Assessment System Terhadap Tingkat Kepatuhan Wajib Pajak Studi kasus Pada KPP Pratama Natar - Hengky Achmad Subing; Asih Pratiwi; Haninun HANINUN (Universitas Bandar Lampung (UBL), 2011)
Tax is the foundation of a source of state revenues, and based on its kind income tax pph ) has given ( largest contribution. Income tax as state revenues collected by the use of a system of self assessment that gives the for taxpayers to count, to reckon; paying and reported own tax terutangnya. The object of this research was conducted in kpp pratama natar-lampung selatan. In this research the use writers collecting data by the use of data resources derived from data the primary and secondary data while a method of collecting data used namely by research kepustakaan, and fieldwork consisting of documentation and quisioner as well as a method of research is the population and sample and analysis used are a descriptive analysis.The results of the test with responses self assessment system according to taxpayers have indicated that variable free in this research have influence quite good against increasing revenue pph followed by increasing the number of tax payers because the implementation of this demanding active taxpayers to count, reckon; pay, and reported taxes payable so that taxpayers play important roles in influence self assessment system against taxpayer compliance rate to kpps natar. Compliance rate in be of various factors this needless in notice to taxpayers the agency can more obedient to pay arrears a tax imposed against taxpayers so the what already exists currently better